2001
DOI: 10.1021/jf010143k
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins and Fumonisins in Corn from the High-Incidence Area for Human Hepatocellular Carcinoma in Guangxi, China

Abstract: A comparative study on the natural occurrence of aflatoxins and Fusarium toxins was conducted with corn samples from high- and low-incidence areas for human primary hepatocellular carcinoma (PHC) in Guangxi, China. In samples from the high-risk area, aflatoxin B(1) was the predominant toxin detected in terms of quantity and frequency, with its concentration ranging between 9 and 2496 microg/kg and an 85% incidence of contamination. Among the samples, 13 (76%) exceeded the Chinese regulation of 20 microg/kg for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(97 citation statements)
references
References 17 publications
2
93
0
2
Order By: Relevance
“…In China, an earlier study suggested the location of high-risk regions along the southeastern coastline, that is in the provinces of Jiangsu, Zhejiang, Fujan, Guangdong and Guangxi Autonomous Region (Yeh et al, 1989). HBV and the dietary aflatoxins have been suggested as the most important HCC hazard factors in China (Li et al, 2001), where HBV infection is almost a prerequisite for the onset of HCC in the high-risk regions (Yeh et al, 1989;Shen et al, 1991). Dietary exposure to aflatoxin B1 (AFB1) (Li et al, 2001;Wang et al, 2001;Wang and Liu, 2007) may associate with HCC risk in Chinese cohorts due to enhancement of the mutation frequency of the third nucleotide of codon 249 of TP53 (Deng et al, 1997;Kirk et al, 2000;Szymanska et al, 2009) and oxidative stress (Wu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, an earlier study suggested the location of high-risk regions along the southeastern coastline, that is in the provinces of Jiangsu, Zhejiang, Fujan, Guangdong and Guangxi Autonomous Region (Yeh et al, 1989). HBV and the dietary aflatoxins have been suggested as the most important HCC hazard factors in China (Li et al, 2001), where HBV infection is almost a prerequisite for the onset of HCC in the high-risk regions (Yeh et al, 1989;Shen et al, 1991). Dietary exposure to aflatoxin B1 (AFB1) (Li et al, 2001;Wang et al, 2001;Wang and Liu, 2007) may associate with HCC risk in Chinese cohorts due to enhancement of the mutation frequency of the third nucleotide of codon 249 of TP53 (Deng et al, 1997;Kirk et al, 2000;Szymanska et al, 2009) and oxidative stress (Wu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…HBV and the dietary aflatoxins have been suggested as the most important HCC hazard factors in China (Li et al, 2001), where HBV infection is almost a prerequisite for the onset of HCC in the high-risk regions (Yeh et al, 1989;Shen et al, 1991). Dietary exposure to aflatoxin B1 (AFB1) (Li et al, 2001;Wang et al, 2001;Wang and Liu, 2007) may associate with HCC risk in Chinese cohorts due to enhancement of the mutation frequency of the third nucleotide of codon 249 of TP53 (Deng et al, 1997;Kirk et al, 2000;Szymanska et al, 2009) and oxidative stress (Wu et al, 2008). However, among R e t r a c t e d individuals at very high risk of liver cancer due to infection with HBV and AFB1 exposure, only 20% eventually develop liver cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes increased the risk of liver cancers in patients with hepatitis and/or cirrhosis and it was concluded and confirmed by a few subsequent reported studies, although the modified factors were different in different studies. 51,62,63 Ei-Serag et al 54 also demonstrated that DM was also shown to increase the risk of primary liver cancers only in the presence of other risk factors such as hepatitis C or B, or alcoholic cirrhosis. In a cohort study, Lai et al 63 found that the association between type 2 DM and incidence of HCC was modified by HCV status after controlling for age, sex, HBV, HCV, smoking, and alcohol consumption.…”
Section: Impact Of Diabetes As Risk Factor In Hepatocellular Carcinomamentioning
confidence: 99%
“…The association between DM and HCC was found to be modified by hepatitis virus infection, heavy alcohol consumption, and other known risk factors. 51,[61][62][63] Fujino et al 2001 61 found that the relative risk (RR) of DM for primary liver cancers was 2.06 (95% CI, 1.01-4.19) after adjustment for smoking, alcohol, and diseases associated with liver cancer in a prospective study of diabetes and liver cancers in Japan. Diabetes increased the risk of liver cancers in patients with hepatitis and/or cirrhosis and it was concluded and confirmed by a few subsequent reported studies, although the modified factors were different in different studies.…”
Section: Impact Of Diabetes As Risk Factor In Hepatocellular Carcinomamentioning
confidence: 99%
“…HBV and the dietary aflatoxins have been suggested as the most important HCC hazard factors in China (Li et al, 2001), where HBV infection is almost a prerequisite for the onset of HCC in the high-risk regions (Yeh et al, 1989;Shen et al, 1991). Dietary exposure to aflatoxin B1 (AFB1) (Li et al, 2001;Wang et al, 2001;Wang and Liu, 2007) may associate with HCC risk in Chinese cohorts due to enhancement of the mutation frequency of the third nucleotide of codon 249 of TP53 (Deng et al, 1997;Kirk et al, 2000;Szymanska et al, 2009) and oxidative stress (Wu et al, 2008). However, among individuals at very high risk of liver cancer due to infection with HBV and AFB1 exposure, only 20% eventually develop liver cancers.…”
Section: Introductionmentioning
confidence: 99%